2005
DOI: 10.1081/lcss-200026837
|View full text |Cite
|
Sign up to set email alerts
|

Establishment of Continuous Critical Levels for Indices of Plant and Presidedress Soil Nitrogen Status in the Potato Crop

Abstract: Critical levels for six plant and pre-sidedress soil nitrogen indices were established for the growing season and their relative accuracy to diagnose the need for supplemental sidedress N was also compared. Field trials were conducted from 1996 to 1998 with irrigated potato in North-eastern Portugal. Fertilizer treatments included several pre-plant and sidedress N rates. Petiole nitrate concentrations (determined by a standard laboratory method and with the portable RQflex reflectometer), leaf N content, leaf … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 25 publications
(55 reference statements)
1
10
0
1
Order By: Relevance
“…6f). This observation was also reported in other studies for potato (Bélanger et al, 2001b; Rodrigues, 2004; Wilson et al, 2009). However, unlike Bélanger et al (2001b), our critical value was considerably increased when soil NH 4 –N was included in the model (85–132 kg N ha −1 ).…”
Section: Resultssupporting
confidence: 90%
“…6f). This observation was also reported in other studies for potato (Bélanger et al, 2001b; Rodrigues, 2004; Wilson et al, 2009). However, unlike Bélanger et al (2001b), our critical value was considerably increased when soil NH 4 –N was included in the model (85–132 kg N ha −1 ).…”
Section: Resultssupporting
confidence: 90%
“…Belanger et al (2001) and Rodrigues (2004) also found that soil NO 3 –N was the best method for potato, and that the inclusion of NH 4 –N did not improve the test. Meisinger et al (1992), however, found that the addition of soil NH 4 –N was advantageous to determining the CV for corn yields and suggested that it more accurately represented the total availability of N to the crop.…”
Section: Resultsmentioning
confidence: 98%
“…Petiole NO 3 –N concentration is a widely accepted method to determine potato plant N status during the growing season (Porter and Sisson, 1991; Belanger et al, 2003; Rodrigues, 2004). Rosen and Eliason (2005) have listed optimal ranges for petiole NO 3 –N concentrations in the Upper Midwest depending on the growth stage of the potato plant and are highlighted in gray in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that estimation of yield and potential for N response in relative terms is possible. Several studies were conducted to improve the relationship between crop yield and sensor readings [65,106,107,[131][132][133], however, their practical application is still in question due to their inconsistent results.…”
Section: Use Of Sensors and Ndvimentioning
confidence: 99%